Theoretical approaches and directions in the research of homelessness: a critical analysis - Bilinović Rajačić, Ana; Čikić, Jovana (Sociološki pregled, 2020)
Homelessness is often explained simplistically and somewhat atheoretically, as a housing problem or as a social welfare issue caused by structural or individual factors. Such dualistic explanations are not quite adequate and policies of prevention and combating homelessness formed under their influence have proven to be inefficient. Thus, we have analyzed three approaches – life-story approach, homelessness pathways approach and the (sub)culture of homelessness – as means for improvement of understanding the overall experience of homelessness (its causes, paths through and from homelessness as well as outcomes). Special attention was given to the analysis of the aspects of selected theories (feminist, poststructuralist, postmodernist and ecological) and pointing to the fruitfulness of their insights while analyzing homelessness. This paper is based on the analysis of the works of the relevant authors/representatives of selected theoretical perspectives and approaches. The aim of this paper is to provide a critical review of the theoretical understanding of homelessness, as well to expand the understanding of this social phenomenon.